Gmae over! - Lampard, Frank (London: Little, Brown Books for Young Readers, 2018)
Magic meets football in this fun-filled series from legendary footballer Frank Lampard, for readers aged 5 and up. Frankie and his team love playing football. There's always time for a game - whether it's real or on-screen! When Frankie is injured just before a five-a-side tournament, he's worried his team will have to pull out. So, when the magic football brings Frankie's gaming avatar through into the real world, it seems like they've got a perfect substitute. But E-Frankie starts to cause lots of trouble on and off the pitch. What will it take to get him back into the game where he belongs? Have you discovered the rest of the series yet? Frankie and his team play football with pirates, dinosaurs, aliens and everything in between!
Keywords: Soccer stories